ESKALASI DAN URGENSI IMPLEMENTASI PEMBELAJARAN TRANSFORMATIF PADA SISTEM PENDIDIKAN DI INDONESIA: SEBUAH TINJAUAN LITERATUR - Syamsurijal (STKIP Subang, 2026)
Indonesia's education system confronts critical challenges demanding paradigmatic transformation in learning approaches to realize the Golden Indonesia 2045 generation. This study aims to analyze the urgency and escalation of transformative learning implementation within Indonesia's education system through comprehensive literature review. The research methodology employs narrative literature review approach by analyzing academic publications from 2021-2025 period sourced from Google Scholar, Scopus, and Sinta databases. Inclusion criteria encompass peer-reviewed journal articles, academic books, and educational policy reports relevant to transformative learning and Indonesian educational reform. Data analysis utilizes narrative synthesis techniques to identify dominant themes, consistent patterns, and knowledge gaps. Research findings reveal that transformative learning offers relevant theoretical framework for responding to educational challenges complexity through fundamental transformation of learners' perspectives, critical thinking development, and community-based learning. Integration of transformative learning within Merdeka Belajar policy requires transformational leadership, continuous educator competency development, and learning ecosystem reconstruction. Despite confronting infrastructure limitations and cultural resistance, transformative learning escalation offers strategic opportunities for national education systemic transformation through multistakeholder collaboration and contextual adoption of global best practices.